Strategi Pendekatan Historis Dan Pragmatis - Achmad Faris Fizabillah; Silvia Damayanti; Muhammad Yasin (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This research examines the "Historical and Pragmatic Approach Strategy" in the context of policy analysis and implementation. The historical approach focuses on tracing policy developments from the past to understand the context and factors that influenced their formation. Meanwhile, the pragmatic approach emphasizes implementing practical solutions that are adaptive to current situations and dynamic needs. Through a combination of these two approaches, this research aims to produce a more comprehensive and responsive policy strategy. This study uses qualitative methods with secondary data analysis from various historical and contemporary policy sources. The research results show that a combination of historical and pragmatic approaches can increase policy effectiveness by enriching understanding of the roots of problems and offering solutions that are relevant and applicable in the current context.